West Indians [Cricket Team] Manchester - Scott and Co., R (My University, 2012)
West Indies Cricket team captained by H.G.B. Austin who led the team to England in 1906 and 1923. Note on back : "The boys in England, 2nd tour, 1906.". Players are back row, left to right; R. Ollivierre, C.S. Morrison, L. Constantine, G. Challenor, J.E. Parker, T. Burton, O.P. Layne, P. Cumberbatch. Middle row, seated left to right; W.E. Harrigan, H.B.G. Austin (Capt.), P.A. Goodman, T.C. Learmond. Front row, seated, left to right C.R. Bancroft, S. G. Smith.
Landscape; black and white
Keywords: Cricket; Cricket players; Postcards; Men; Uniforms; Ollivierre, Richard; Morrison, Charles Stuart; Constantine, Lebrun; Challenor, George; Parker, John Ernest; Burton, Tommie; Layne, Oliver; Cumberbatch, Archie; Harrigan, Bertie; Austin, Harold Bruce Gardiner; Goodman, Percy Arnold; Learmond, George; Bancroft, Claude; Smith, Sydney Gordon